THE STUDY OF CHARACTERIZATION OF THE MAIN CHARACTER IN BRAVE MOVIE - Kadek Rizka Indah Pratiwi; Made Iwan Indrawan Jendra; I Gusti Bagus Wahyu Nugraha Putra (IJELAL (International Journal of English Learning and Applied Linguistics), 2021)
This study is entitled “The Study of Characterization of the Main Character in Brave movie”. This research is focused on the characterization approach based on the three dimensions of the main character and intrinsic components in the movie. The main purpose of the research is to determine how the author describes the main character in terms of physiological, psychological, and sociological dimensions. The data for this study was collected using the documentation technique, which was based on library research. The obtained data were then descriptively analyzed using the descriptive qualitative method. This study uses theory from Kenney (1966) to explain category the main character and for theory of three dimension of characterization proposed by Egri (1985). The data source of this study is a movie entitled Brave (2012). Based on Kenney’s theory, the writer found that the main character in Brave movie as dynamic character. In addition, based on Egri’s theory, there are three dimensions (physiological, psychological, and sociological) involved in the shaping and presentation of the main character. The result after doing analyzing this study there was found 8 data of dimension of characterization, including Psychological with 5 data, Physiological with 2 data, and Sociological with 1 data